PENGARUH PEMBELAJARAN TGFU DAN KOOPERATIF TERHADAP HASIL BELAJAR KETERAMPILAN DASAR SEPAKBOLA DENGAN KEMAMPUAN MOTORIK TINGGI DAN KEMAMPUAN MOTORIK - Luqman Hakim (STKIP Subang, 2017)
The purpose of this study examine the influence TGFU and Cooperative learning model as well as motor skills to learn results of football basic skills. The learning model Teaching Games for Understanding and Cooperative learning grouped by high and low of motor skills. The method used in this study using an experimental method with 2x2 factorial design. The study was conducted in Muhammadiyah Kab. Garut junior high school. The population is all class VIII students of Muhammadiyah junior high school. The sampling technique used in this research is purposive random sampling. The sample in this study amounted to 48 students were divided into 4 groups. Instruments in this study include: (1) Barrow mototr ability test to measure motor skills, (2) Test of football basic skills. ANOVA analysis results indicate, cooperative learning and TGFU model give influence on the learn result the basic skills of football. There is interaction between the learning model and motor ability of football basic skills.TGFU learning model at a high level motor skills provide better influence to learn result of football basic skills. Cooperative learning model is better than the TGFU at a low level of motor skills to learn result of football basic skills.